The modified Adomian decomposition method for solving Chaotic Lü system - Razali, Nur Iznida; Chowdhury, M. S. H.; Asrar, Waqar (2012)
In this paper, a numerical scheme based on adaption of standard adomian decomposition method (ADM) is applied to thechaotic Lü system. Then, the standard ADM is converted into a hybrid numeric-analytic method called the modified ADM (MADM). Numerical comparisons with the standard ADM and the fourth-order Runge-Kutta method (RK4) is made in order to prove that MADM is the reliable method for nonlinear problems.